Ethics of Care in Laudato Si’: A Postcolonial Ecofeminist Critique - Brazal, Agnes M. (Feminist theology, 2021)
This article engages with the care ethics of Laudato Si’ through the lens of postcolonial ecofeminism. Laudato Si’ speaks of the family of creation where nature is both a nurturing mother and a vulnerable sister, reflecting patriarchal associations of women with nature, fragility, and the virtue of care. This indirectly undermines the need for men to engage in care/social reproduction work as well as the strengthening of women’s agency. While this kin-centric ecology acknowledges the interdependence of creatures, it maintains the hierarchy of humans over nature and underlines this family’s headship by an all-powerful Father. Laudato Si’s family ecology and God language inadvertently reifies women–nature–care connection and reinforces the logic of male domination. This study recommends exploring gender inclusive images of the Trinity and the family of creation in mutual relations to foster care that promotes both the agency of women and nature.